IDENTIFIKASI KARAKTERISTIK PENYAKIT PENYERTA PADA PENDERITA COVID-19 DI INDONESIA - iis suryani; Wulan Angraini; Sarkawi (Avicenna: Jurnal Ilmiah, 2023)
Background: Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by the new Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus which was first detected in Wuhan City of China and spread widely to more than 180 countries in the world . Given the high number of Covid-19 cases both globally and nationally, this study aims to identify the characteristics of co-morbidities in patients with Covid-19. Method: This research is a qualitative descriptive research using secondary data through the official website covid.go.id. Results: a descriptive study through the official government website showed that the majority of Covid-19 sufferers were dominated by women (51.3%) with most of the deaths occurring in the age group > 60 years (46.7%) and the majority of Covid-19 patients suffered hypertension (50%) and diabetes mellitus (37.2%). Conclusions and Suggestions: Most of the co-morbidities in patients with Covid-19 in Indonesia occur in the age group >60 years with chronic disease conditions, the majority being hypertension and diabetes mellitus. So, as a self-defense effort, giving vaccines to co-morbid groups must still be carried out by following the technical instructions for implementing the Covid-19 vaccine.